SNAREs define targeting specificity of trafficking vesicles by combinatorial interaction with tethering factors - Koike, Seiichi (Nat Commun, 2019)
Membrane traffic operates by vesicles that bud from precursor organelles and are transported to their target compartment where they dock and fuse. Targeting requires tethering factors recruited by small GTPases and phosphoinositides whereas fusion is carried out by SNARE proteins. Here we report that vesicles containing the Q-SNAREs syntaxin 13 (Stx13) and syntaxin 6 (Stx6) together are targeted to a different endosomal compartment than vesicles containing only Stx6 using injection of artificial vesicles. Targeting by Stx6 requires Vps51, a component of the GARP/EARP tethering complexes. In contrast, targeting by both Stx6 and Stx13 is governed by Vps13B identified here as tethering factor functioning in transport from early endosomes to recycling endosomes. Vps13B specifically binds to Stx13/Stx6 as well as to Rab14, Rab6, and PtdIns(3)P. We conclude that SNAREs use a combinatorial code for recruiting tethering factors, revealing a key function in targeting that is independent of SNARE pairing during fusion.